Determinants of migration decisions among medical personnel in Poland: between economics, work organization and professional prestige - Badora-Musiał, Katarzyna; Paszko, Weronika; Kwilosz, Edyta; Domagała, Alicja (Polish Journal of Public Health, 2026)
Introduction. Migration of medical personnel is a global phenomenon intensified by workforce shortages and posing major challenges for health policy. Analysing this issue is essential for developing effective, evidence-based retention strategies to mitigate escalating workforce shortages and ensure the stability of the national healthcare system. Aim. This study aimed to identify factors influencing migration decisions among Polish healthcare workers. Materials and methods. A cross-sectional online survey was conducted between February and May 2025 among 112 medical professionals. Statistical analysis employed the χ² test and the Fisher-Freeman-Halton test (α = 0.05). Results. Low remuneration (61.6%), difficult working conditions and limited professional development were the main push factors. Higher salaries, better working conditions, and improved quality of life were the main pull factors. Poorer evaluations of working conditions were significantly associated with migration intentions (p = 0.0174). Younger age (under 34 years; p = 0.0137) and shorter professional experience (≤5 years; p = 0.0078) increased the likelihood of considering emigration. Unexpectedly, overtime work was associated with a lower willingness to emigrate (p < 0.0001), while higher perceived professional prestige had a protective effect (p = 0.0381). Conclusions. Migration decisions among Polish healthcare workers are driven primarily by economic and organizational factors. Effective retention requires integrated strategies combining wage improvements with better working conditions and initiatives enhancing the prestige of medical professions.